De la lecture des graphies synthétiques de noms de couronnement ptolémaïques - Habachy, Mounir (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
In the present study, when a comparison is made between the combination of divine attributes s ḫ m and onX represented at the end of the “long complete” cartouches, and those held by the divinities inside “synthetic complete” cartouches of Ptolemy V and Ptolemy XII, the reading sXm-onX-Jmn is acceptable. But, when the same method is applied to the cartouches of Ptolemy IX Soter II, the reading becomes problematic. We are trying, then, to examine the reading of the Coronation name of this king.